Представления о справедливости в России и в Украине: повседневность и идеология - Кирюхин, Д.; Щербак, С. (Социология: теория, методы, маркетинг, 2007)
It is the first comparative study of the representations of justice in Ukraine and in Russia. The research shows that ethical notion of justice predominate in Russia and in Ukraine. It says that in both countries the characteristic for traditional societies system of norms and values prevails. Bedsides, there are some significant differences between Russians and Ukrainians in the representation of justice. Russians people more often than Ukrainians defines justice as a category of law. It is evidence of development the different models of political culture in both countries (under the influence of dominating ideology) — aligned with state in Russian and aligned with society in Ukraine. Ideology of national revival and rehabilitation of historical justice peculiar to Ukraine opposes to ideology of sovereign democracy in Russia.